Exploring the impact of firm- and relationship-specific factors on alliance performance: Evidence from Turkey - A. Esen; G. Alpay (South African Journal of Business Management, 2017)
This study investigates the impact of firm-specific (i.e., alliance orientation and partner selection criteria) and relationship-specific (i.e., strategic fit, cultural fit, and organizational fit) factors on alliance performance and assesses the mediating role of trust in the relationship between relationship-specific factors and alliance performance. Partial least squares analysis is applied to a data set of 106 strategic alliances, including both equity alliances (joint ventures) and non-equity alliances (contractual alliances). The empirical results reveal that alliance orientation and strategic fit lead to superior alliance performance and that cultural fit is positively related to partner trustworthiness. The results have managerial implications regarding how to maximize the positive outcomes of an alliance.
Keywords: 650